Peroxynitrite decomposition catalyst prevents MMP activation and neurovascular injury after prolonged cerebral ischemia in rats - Suofu, Yalikun (2010)
Matrix metalloproteinases (MMPs) play an important role in reperfusion-induced brain injury following ischemia. To define the effects of peroxynitrite decomposition catalyst on MMP activation and neurovascular reperfusion injury, FeTMPyP (5,10,15,20-tetrakis (2,4,6-trimethyl-3,5-disulfonatophenyl)-porphyrin iron (III)) was administered intravenously 30 min prior to reperfusion following a middle cerebral artery occlusion (MCAO). Activation of MMP was assessed by in situ and gel zymography. Neurovascular injury was assessed using endothelial barrier antigen (EBA), collagen IV immunohistochemistry and Cresyl violet staining. Results were compared to sham and ischemia alone groups. We found that administration of FeTMPyP just before reperfusion after ischemia inhibited MMP-9 activation and total MMP-2 increases in the cortex and decreased active MMP-9 along with the total amounts of active MMP-9 and active MMP-2 in the striatum. Reperfusion-induced injury to the basal lamina of collagen IV-immunopositive microvasculature and neural cells in cortex and striatum was ameliorated by FeTMPyP. Losses of blood vessel endothelium produced by ischemia or reperfusion were also decreased in the cortex. These results suggest that administration of FeTMPy prior to reperfusion decreases MMP activation and neurovascular injury after prolonged cerebral ischemia. This strategy may be useful for future therapies targeted at preventing breakdown of the blood-brain barrier and hemorrhagic transformation.